2016
DOI: 10.1080/09205063.2016.1221700
|View full text |Cite
|
Sign up to set email alerts
|

Poly(γ-glutamic acid), coagulation? Anticoagulation?

Abstract: Poly(γ-glutamic acid) (γ-PGA) powder was usually used as hemostatic agent because of its excellent physical properties of water-absorption and water-locking. However, if γ-PGA absorbs enough water, how about its blood compatibility? Here, the other side of the coin was investigated. The anticoagulant properties of γ-PGA were characterized by in vitro coagulation tests, hemolytic assay, platelet adhesion, and platelet activation. Moreover, cytotoxicity experiments of γ-PGA were also carried out by MTT assay. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The results are consist with a previous study. 33 In Figure 3(b), we can see that the fluorescence intensity of 4-PEG(G 3 ) 4 /NK (1/1) was approximately the same as NK, which suggests that the fluorescence spectrum of tryptophan residue in NK was not changed and its conformation was as same as pure NK. The secondary and tertiary structures of NK and 4-PEG(G 3 ) 4 /NK (1/1) were investigated by CD spectra [Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The results are consist with a previous study. 33 In Figure 3(b), we can see that the fluorescence intensity of 4-PEG(G 3 ) 4 /NK (1/1) was approximately the same as NK, which suggests that the fluorescence spectrum of tryptophan residue in NK was not changed and its conformation was as same as pure NK. The secondary and tertiary structures of NK and 4-PEG(G 3 ) 4 /NK (1/1) were investigated by CD spectra [Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The negative charges in polyglutamic acid attracts more NK in x ‐PEG(G 3 ) x /NK, as verified by the increased size and decreased zeta potential (Supporting Information Table S1). The results are consist with a previous study . In Figure (b), we can see that the fluorescence intensity of 4‐PEG(G 3 ) 4 /NK (1/1) was approximately the same as NK, which suggests that the fluorescence spectrum of tryptophan residue in NK was not changed and its conformation was as same as pure NK.…”
Section: Resultsmentioning
confidence: 99%
“…In 2001, Subramanian and colleagues made a seminal discovery by demonstrating that γ-PGA can establish a water environment through hydration repulsion with cationic lipid membranes, marking a pivotal advancement in drug delivery [ 7 ]. Xu and his team found that γ-PGA, with its exceptional water absorption capacity, exhibits anticoagulant properties, holding significant promise for future applications in conditions such as thrombosis [ 8 ]. As a result of its eco-friendly nature and outstanding properties, γ-PGA has emerged as a focal point of research, with its application domains continuously expanding.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer is also known to have good adherence to the metallic surface. All these properties of PGA motivated us to test it as a cover layer for FePd surfaces [ 17 ]. For the deposition of the polymers on the metal surface, the latter was treated with cold plasma.…”
Section: Introductionmentioning
confidence: 99%